2023
DOI: 10.1051/0004-6361/202244875
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the host galaxy ages of X-ray selected AGN in COSMOS

Abstract: We explore the properties of the host galaxies of X-ray selected AGN in the COSMOS field using the Chandra Legacy sample and the LEGA-C survey VLT optical spectra. Our main goal is to compare the relative ages of the host galaxies of the obscured and unobscured AGN by means of the calcium break D n (4000) and the H δ Balmer line. The host galaxy ages are examined in conjunction with other properties such as the galaxy stellar mass, and star-formation rate as well as the AGN Eddington ratio. Our sample consists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 126 publications
13
14
0
Order By: Relevance
“…These studies have shown that X-ray absorbed AGN exhibit, on average, lower n Edd compared to their X-ray unabsorbed counterparts (Ricci et al 2017;Ananna et al 2022;Georgantopoulos et al 2023), in agreement with our findings.…”
Section: Obscuration and Eddington Ratiosupporting
confidence: 93%
See 3 more Smart Citations
“…These studies have shown that X-ray absorbed AGN exhibit, on average, lower n Edd compared to their X-ray unabsorbed counterparts (Ricci et al 2017;Ananna et al 2022;Georgantopoulos et al 2023), in agreement with our findings.…”
Section: Obscuration and Eddington Ratiosupporting
confidence: 93%
“…Mountrichas et al (submitted) built upon these insights by employing X-ray AGN data from the 4XMM catalog and implementing rigorous X-ray criteria for AGN classification. Their results closely mirrored those obtained by Georgantopoulos et al (2023), reinforcing the observed differences in host galaxy properties between X-ray obscured and unobscured AGN. Moreover, their analysis highlighted that these distinctions tend to diminish for luminous AGN.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings align with this trend, yet the distinction is less prominent, despite being consistently observed across various L X . Previous studies have found differences in the SFR of AGN host galaxies for different obscuration levels, in particular for AGN with modest L X (Georgantopoulos et al 2023;Mountrichas & Georgantopoulos 2024;Mountrichas et al 2024b). The COSMOS field benefits from deeper observations compared to the XMM-XXL, resulting in a higher number of AGN in COSMOS that exhibit elevated obscuration levels.…”
Section: Comparison Of the Sfr Of Agn And Non-agn Galaxies As A Funct...mentioning
confidence: 95%